Structural Modeling of the Relationships Between Academic Perfectionism and the Psychosocial Structure of the Classroom on Feelings of Academic Incompetence with the Mediating Role of Academic Self-Handicapping in Secondary School Students - Enayat Sani, Mohammad; Haydari, Shaban; Kazem Fakhri , Mohammad (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the structural relationships between academic perfectionism and psychosocial classroom structure with feelings of academic incompetence through the mediating role of academic self-handicapping among upper secondary school students. This study employed a correlational design using structural equation modeling SEM. The statistical population consisted of all male and female upper secondary school students in Gorgan during the 2025–2026 academic year. Based on structural modeling criteria and the number of observed variables, a sample of 405 students was selected through multistage cluster sampling. Data were collected using the Academic Perfectionism Questionnaire, Psychosocial Classroom Structure Questionnaire, Academic Self-Handicapping Questionnaire, and the researcher-made Feelings of Academic Incompetence Questionnaire. Data analysis was performed using descriptive statistics, Shapiro–Wilk test, Durbin–Watson test, confirmatory factor analysis, structural equation modeling, and bootstrap analysis in SPSS and AMOS software. The findings indicated that academic perfectionism had a significant direct effect on feelings of academic incompetence β = -0.230, p < 0.01. Psychosocial classroom structure also significantly predicted feelings of academic incompetence β = -0.295, p < 0.001. However, the direct effect of academic self-handicapping on feelings of academic incompetence was not significant β = 0.015, p > 0.05. In addition, the indirect effects of academic perfectionism and psychosocial classroom structure on feelings of academic incompetence through academic self-handicapping were not statistically significant. The results further demonstrated that although several direct structural paths were significant, the overall fit indices of the structural model did not reach acceptable thresholds. The findings suggest that both academic perfectionism and psychosocial classroom structure play important roles in shaping students’ feelings of academic incompetence.